Impact of medication adherence to dual antiplatelet therapy on the long-term outcome of drug-eluting or bare-metal stents. (25th November 2020) - Choi, J.H; Choi, J.M; Lee, S.H; Jang, Y.J; Kang, M; Lee, J.M; Park, T.K; Yang, J.H; Song, Y.B; Choi, K.H; Hahn, J.Y; Choi, S.H; et al.
Abstract: Objective: In percutaneous coronary intervention, drug-eluting stent (DES) showed better clinical outcome compared to bare-metal stent (BMS) but mostly with different DAPT durations. This study investigated the clinical superiority of DES over BMS with regard to the medication adherence to dual antiplatelet therapy (DAPT). Methods: We retrospectively enrolled all Koreans PCI patients in year 2011 (n=47, 291). Medication adherence to DAPT was assessed by proportion of days covered (PDC) per 6 months. Analysis adjusted with the clinical propensity for receiving DES or BMS and DAPT PDC of the first 6 month was performed. Primary outcome was the 5-year major adverse clinical event (MACE) risk consisting all-cause death, revascularization, shock, or stroke. Results: Patients with DES (n=46, 356) showed higher PDC (78% versus 60%, p<0.001) and lower MACE risk (39% versus 56%, p<0.001) compared to patients with BMS (n=935). In the propensity-matched 1, 868 patients, MACE risk was lower with DES than BMS (46% versus 54%, HR=0.80, 95% CI: 0.70–0.91, p<0.001). Patients with good medication adherence (PDC ≥80%) showed much lower MACE risk compared to patients with PDC <80% regardless of DES or BMS (HR=0.36, 95% CI: 0.30–0.44; HR=0.40, 95% CI: 0.33–0.48, p<0.001, all). Patients with DES and PDC <80% showed higher MACE risk compared to BMS with and PDC ≥80% (HR=1.30, 95% CI: 1.03–1.64, p=0.027). Conclusions: Good medication adherence to DAPT in the first 6 month was prerequisite for better clinical outcome in both DES and BMS. DES with poor adherence to DAPT showed worse outcome compared with BMS with good adherence. Funding Acknowledgement: Type of funding source: None